Cr-N co-doped ZnO nanoparticles: synthesis, characterization and photocatalytic activity for degradation of thymol blue - A. Nibret; O. P. Yadav; I. Diaz; A. M. Taddesse (Bulletin of the Chemical Society of Ethiopia, 2015)
Here we report the synthesis of CrN co-doped ZnO for the first time. Zinc oxide (ZnO) nanoparticles were synthesized by direct precipitation method via the reaction between zinc nitrate [Zn(NO3)2 .6H2O] and ammonium carbonate [(NH4)2CO3] in aqueous solutions with proper concentration. Modified photocatalysts were synthesized by the incipient wetness impregnation method (chromium-doped ZnO) and by solid state reactions using ZnO and urea as precursors (nitrogen-doped ZnO). Chromium-nitrogen co-doped ZnO nanomaterials were prepared from the already prepared N-doped ZnO nanomaterials via one step impregnation method. The as-synthesized photocatalysts were investigated by XRD, BET, SEM-EDX, FTIR, and UV–Vis techniques. Photocatalytic degradation of thymol blue using as-synthesized photocatalysts was studied under visible as well as UV irradiations. Highest photocatalytic degradation efficiency of chromium-nitrogen co-doped zinc oxide could be attributed to the lower rate of recombination of the photo-generated electrons and holes as well as to its lower band gap energy as the result of the co-doping. Photocatalytic degradation is found to follow pseudo first order kinetics.